2014
DOI: 10.1155/2014/679810
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Knowledge and Formulations of Medicinal Plants Used by the Traditional Medical Practitioners of Bangladesh to Treat Schizophrenia Like Psychosis

Abstract: Schizophrenia is a subtle disorder of brain development and plasticity; it affects the most basic human processes of perception, emotion, and judgment. In Bangladesh the traditional medical practitioners of rural and remote areas characterized the schizophrenia as an insanity or a mental problem due to possession by ghosts or evil spirits and they have used various plant species' to treat such symptoms. The aim of the present study was to conduct an ethnomedicinal plant survey and documentation of the formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…During recent years, complementary and alternative medicine (CAM) has become more popular worldwide. Many plant species have emerged as herbal medicines, and their active components have been subjected to extensive scientific research around the world [3][4][5]. CAM or traditional medicines are considered safe and effective in sensitive and complicated diseases like CNS disorder, while having less side effects than synthetic compounds [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During recent years, complementary and alternative medicine (CAM) has become more popular worldwide. Many plant species have emerged as herbal medicines, and their active components have been subjected to extensive scientific research around the world [3][4][5]. CAM or traditional medicines are considered safe and effective in sensitive and complicated diseases like CNS disorder, while having less side effects than synthetic compounds [6].…”
Section: Introductionmentioning
confidence: 99%
“…K.Schum. Holde, Korobi Shrub Bark, seed Schizophrenia Anti-acetylcholinesterase [ 4 , 123 ] Araceae Alocasia macrorrhizos (L.) G.Don Mankachu forb/herb Petiole Mental disorder NRE [ 124 ] Colocasia esculenta (L.) Schott Mukhikachu Forb/herb Whole plant Nervous system disorder Nerve tonic [ 14 , 125 ] Pothos scandens L. Sunat Epiphyte Leaves Migraine, vertigo NRE [ 101 ] Typhonium trilobatum (L.) Schott Ghetkaachu Herb Whole plant Nervous debility, mental disorder NRE [ 89 , 126 ] Xanthosoma violaceum Schott Shada kochu Forb/herb Tuber Alzheimer’s disease (Ga) Antinociceptive [ 127 , 128 ] Araliaceae Schefflera roxburghii Gamble Den anno Tree Leaves Insomnia NRE …”
Section: Introductionmentioning
confidence: 99%
“…Traditional medicine is practiced in Bangladesh by folk medicine practitioners, also known as Kabirajes who utilize various formulations of medicinal plants in most of their preparations. We have observed that the Kabirajes of various districts and areas use diverse varieties of plants for the treatment of schizophrenia and psychotic problems [11], cardiovascular problems [12], eye infections [13], snakebite [14], diabetes [15], gastrointestinal disorders [16, 17], HIV/AIDS related infections [18], rheumatoid arthritis [19], cattle diseases [20], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…After 30 min of amphetamine organization, the creature was put on the internal top of the pen and cover was shut 16 . Amphetamine does not incite unconstrained climbing conduct as apomorphine does and subsequently when the amphetamine treated creature is set on the top of the enclosure, it stayed on it for a more drawn out time while the saline treated creature will promptly go down to the base 17 . The aggregate time spent on the inward top/mass of the pen was estimated for 30min.The force of stereotyped conduct of individual mice was scored at 15 minutes interims for a time of 60 min.…”
Section: Amphetamine Induced Stereotypic Behaviour In Micementioning
confidence: 99%